2017
DOI: 10.1080/20013078.2017.1378056
|View full text |Cite
|
Sign up to set email alerts
|

Neutral sphingomyelinases control extracellular vesicles budding from the plasma membrane

Abstract: Extracellular vesicles (EVs) are membrane particles secreted from cells into all body fluids. Several EV populations exist differing in size and cellular origin. Using differential centrifugation EVs pelleting at 14,000 g (“microvesicles” (MV)) and 100,000 g (“exosomes”) are distinguishable by protein markers. Neutral sphingomyelinase (nSMase) inhibition has been shown to inhibit exosome release from cells and has since been used to study their functional implications. How nSMases (also known as SMPD2 and SMPD… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

13
205
2
7

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 258 publications
(242 citation statements)
references
References 40 publications
13
205
2
7
Order By: Relevance
“…Ceramide is involved in MVE formation, and as originally reported by Trajkovic et al, blocking of ceramide synthesis by inhibition of neutral sphingomyelinase‐2 (nSmase2) has been widely used to interfere with exosome production. By contrast, nSmase2 inhibition does not prevent and can instead enhance the production of ectosomes …”
Section: Resultsmentioning
confidence: 94%
See 1 more Smart Citation
“…Ceramide is involved in MVE formation, and as originally reported by Trajkovic et al, blocking of ceramide synthesis by inhibition of neutral sphingomyelinase‐2 (nSmase2) has been widely used to interfere with exosome production. By contrast, nSmase2 inhibition does not prevent and can instead enhance the production of ectosomes …”
Section: Resultsmentioning
confidence: 94%
“…By contrast, nSmase2 inhibition does not prevent and can instead enhance the production of ectosomes. 40 In order to characterize the origin of the EVs involved in Hck-activated vesicle secretion of TACE we generated knock-down derivatives of HEK293 cells in which nSmase2 expression had been suppressed by lentivirally delivered shRNAs. We found that similar to the spontaneous EV secretion of LAMP-1, Hck-activated packaging of TACE into EVs was almost completely blocked as a consequence of the Smase2 knock-down ( Figure 6).…”
Section: Tace-containing Evs Are Produced By An Nsmase2-dependent Ementioning
confidence: 99%
“…Wang et al, 2012). To date, inhibition or genetic deficiency of nSMase2 is a method widely used to prevent exosome secretion in various cell types and tissues (Chairoungdua, Smith, Pochard, Hull, & Caplan, 2010; Dinkins et al, 2014; Dinkins, Enasko, et al, 2016; Dinkins, Wang, & Bieberich, 2016; Goldkorn, Chung, & Filosto, 2013; Guo, Bellingham, & Hill, 2015; Kong, He, et al, 2015; Kosaka et al, 2010; Marsh & van Meer, 2008; Menck et al, 2017; Shamseddine, Airola, & Hannun, 2015; Tan et al, 2013; Trajkovic et al, 2008; Yuyama, Sun, Mitsutake, & Igarashi, 2012). nSMase2 converts sphingomyelin into ceramide, a reaction shown to be instrumental for exosome secretion in vitro (Trajkovic et al, 2008) (Fig.…”
Section: Got Exosomes: What’s (Really) In Your Prep?mentioning
confidence: 99%
“…1L). Further analysis with successive differential ultracentrifugation of pellets from conditioned media, a strategy that effectively separates sEVs from MVs (14,000 g and 100,000 g of sedimentation, respectively) 28 , indicated enhanced secretion of sEVs by SEN cells, while MV release remained largely unchanged, implying engagement of a mechanism specifically responsible for production of sEVs, but not all EV subtypes (Fig. 1M).…”
Section: Senescent Stromal Cells Generate An Increased Number Of Evsmentioning
confidence: 99%